Height-dependent variation in corticospinal excitability modulation after active but not sham intermittent theta burst stimulation - Tomeh, Abdulhameed; Yusof Khan, Abdul Hanif Khan; Abu Zaid, Zalina; Ling, King Hwa; Inche Mat, Liyana Najwa; Basri, Hamidon; Wan Sulaiman, Wan Aliaa (Elsevier, 2025)
Poor reproducibility and high inter-individual variability in responses to intermittent theta burst stimulation (iTBS) of the human motor cortex (M1) are matters of concern. Here we recruited 17 healthy young adults in a randomized, sham-controlled, crossover study. Transcranial magnetic stimulation (TMS)-elicited motor evoked potentials (MEPs) were measured pre-iTBS (T0) and post-iTBS at 4–7 (T1), 9–12 (T2), 17–20 (T3), and 27–30 minutes (T4) from the right first dorsal interosseous muscle. MEP grand average (MEPGA) was defined as the mean of the normalized-to-baseline MEPs at all timepoints post-iTBS. As secondary objectives, we measured blood pressure, heart rate, and capillary blood glucose pre-iTBS, and at 0 and 30 minutes post-iTBS. The TMSens_Q structured questionnaire was filled out at the end of each session. Two-way repeated ANOVA did not show a significant TIME×INTERVENTION interaction effect on MEP amplitude, MEP latency, blood pressure, heart rate, and blood glucose (p > 0.05). Sleepiness was the most reported TMSens_Q sensation (82.3 %) in both groups. Surprisingly, the subjects’ height negatively correlated with the normalized MEP amplitudes at T3 (r = -0.65, p = 0.005), T4 (r = -0.66, p = 0.004), and MEPGA (r = -0.68, p = 0.003), with a trend correlation at T1 (r = -0.46, p = 0.062) and T2 (r = -0.46, p = 0.065) in the active but not sham group. In view of this, we urge future studies to delve deeper into the influence of height on neuroplasticity induction of the M1 representation of peripheral muscles. In the end, we highlight unique methodological considerations in our study protocol and future recommendations for M1-iTBS studies.